2020
DOI: 10.1007/s10461-020-02976-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Influences of the COVID-19 Pandemic on Drug Use and HIV Care Among People Living with HIV and Substance Use Disorders: Experience from a Pilot mHealth Intervention

Abstract: People living with HIV (PLWH) and substance use disorder (SUD) are particularly vulnerable to harmful health consequences of the global COVID-19 pandemic. The health and social consequences of the pandemic may exacerbate substance misuse and poor management of HIV among this population. This study compares substance use and HIV care before and during the pandemic using data collected weekly through an opioid relapse prevention and HIV management mobile-health intervention. We found that during the pandemic, PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 18 publications
3
98
0
3
Order By: Relevance
“…18 52 People with HIV Nineteen studies assessed PLHIV. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Three modelling studies predicted a significant increase in HIV-related deaths in African countries due to treatment disruption with the pandemic. [61][62][63] A US retrospective observational quantitative study found that shelter-inplace orders had a negative impact on antiretroviral therapy adherence, especially among homeless PLHIV.…”
Section: General Publicmentioning
confidence: 99%
“…18 52 People with HIV Nineteen studies assessed PLHIV. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Three modelling studies predicted a significant increase in HIV-related deaths in African countries due to treatment disruption with the pandemic. [61][62][63] A US retrospective observational quantitative study found that shelter-inplace orders had a negative impact on antiretroviral therapy adherence, especially among homeless PLHIV.…”
Section: General Publicmentioning
confidence: 99%
“…On the other hand, concomitant antiretroviral therapy- (ART) non-adherence and decreased confidence in attending HIV follow-up visits have also been reported to be growing [ 21 ]. Rising evidence is also corroborating the potential surge in opioid overdose among PWID and decrease in bystander rescue during the pandemic [ 21 23 ] which can also potentially be due to medication unavailability. This pool of dynamics, coupled with the closure of substance abuse clinics and the reallocation of services to support COVID-19 efforts, could result in deleterious effects on HIV prevention efforts and HIV transmission [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of ongoing challenges in harm reduction programs such as the closure of syringe service programs (SSPs) or significant reductions in SSP working hours [ 25 ], PWID are at increased risk for HIV transmission and opioid overdoses that could be lethal, as discussed earlier. As in-person meetings with medical providers are limited during the COVID-19 pandemic, mHealth interventions could constitute a suitable alternative to deliver care to PLWH and patients with OUD as they have a high level of satisfaction from both patient and provider perspectives [ 21 , 26 ]. Telehealth services should therefore be encouraged when available and amenable to be delivered in an appropriate manner [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although governments are rightfully focused on controlling transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), marginalized populations struggle to maintain access to harm reduction and drug treatment services (5)(6)(7)(8). Beyond interfering with HCV elimination efforts, the pandemic may, through increased inequity and changes to social service and community support structures, exacerbate existing challenges faced by these groups, including stigma and discrimination, overdose risk, comorbidities, poverty, precarious housing, and domestic violence (9)(10)(11)(12). Recent increases in overdose-related deaths in North America reflect this reality (13)(14)(15).…”
Section: To the Editormentioning
confidence: 99%